PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VA SDN 011 MEKAR SARI - Ningsih, Surya Ningsih; Alpusari, Mahmud Alpusari; ', Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract. This research represent the Research of Class Action (CAR) done to increase result of learning student of class of VA  SDN 011 Mekar Sari  by applying model the study of co-operative of type of Teams of Games Tournament (TGT). This Research is conducted at April 2014 executed by 2 cycle. this Subjek Research is student of class of VA SDN 011 Mekar Sari  amounting to 27 one who is  made by a data source. Instrument of data collecting at this research is sheet of activity perception learn and student and also result of learning. Mean of result of learning previous student that is 55,2 from 27 complete student people only 7 completely is klasikal 25,9% while student which is not complete 20 people completely is klasikal 74,1%. At this research is presented by a activity percentage learn and student and also result of daily restating of  cycle of I and cycle II. Activity Percentage learn at cycle of I and II is 45,9% mounting to become 81%. percentage of student Activity of at cycle of I and II is 48,2% mounting to become 73,2% Mean of  result of learning student of at  cycle I is 71,3 from 27 student, complete 23 people with the percentage 85,2% and which is not complete 4 people with the percentage 14,8%. Mean of result of learning student of cycle II is 90,3 from 27 one who complete 26 people with the percentage 96,3%. Inferential thereby that this research hypothesis that is if applied by model of study of co-operative of type of Teams of Games Tournament (TGT). hence can improve the result learn the student of class of VA SDN 011 Mekar Sari  accepted. Keywords : Model The Study of Co-Operative of Type of Teams of Games Tournament, Result of Learning Sains.